Types and Meanings of Idiomatic Expression Used in Bruno Mars Song - Etika Ariyani (Muhammadiyah University of Mataram, 2021)
This paper examines types of idiom and meaning that found in song lyric of Bruno Mars. In clarifying the meaning of idiom, it is not only find the word from the contextual meaning but also the speakers condition when uttering the message. This study was conducted using a descriptive qualitative approach focusing on idiomatic expressions and meanings. This study is a qualitative research and data was taken from Bruno Mars album. The researcher used Siedl and Mc Mordie theory to investigate the type of idioms and meanings. From the findings, there are four types of idiom found such as special categories, noun with preposition, verb with preposition and preposition with adverb.The idiom meaning had strong message that delivered in the song. In order to investigate the meaning of idiom that found in Bruno Mars lyrics, the researcher used Leech theory and found two types of meaning in Bruno Mars song lyric